International Symposium on “New Sources, New Approaches, New Theories: Reinvigorating Research on Modern Sino-Foreign Cultural Exchange” Conference Summary - NIE, Li (Journal of Research for Christianity in China (JRCC), 2023)
Conference Dates: December 9–10, 2023 Venue: Central China Normal University Theme: New Sources, New Methods, New Theories: Reinvigorating Research on Modern Sino-Foreign Cultural Exchange